2013
DOI: 10.1002/jgrd.50480
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric CH4 in the first decade of the 21st century: Inverse modeling analysis using SCIAMACHY satellite retrievals and NOAA surface measurements

Abstract: [1] The causes of renewed growth in the atmospheric CH 4 burden since 2007 are still poorly understood and subject of intensive scientific discussion. We present a reanalysis of global CH 4 emissions during the 2000s, based on the TM5-4DVAR inverse modeling system. The model is optimized using high-accuracy surface observations from NOAA ESRL's global air sampling network for 2000-2010 combined with retrievals of column-averaged CH 4 mole fractions from SCIAMACHY onboard ENVISAT (starting 2003). Using climatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
397
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 291 publications
(427 citation statements)
references
References 77 publications
29
397
1
Order By: Relevance
“…Pison et al, 2013) or for a limited number of flux categories (e.g. Bergamaschi et al, 2013). Indeed, the assimilation of CH 4 observations alone, as reported in this synthesis, cannot fully separate individual sources, although sources with different locations or temporal variations could be resolved by the assimilated atmospheric observations.…”
Section: Definition Of Regions and Source Categoriesmentioning
confidence: 88%
See 1 more Smart Citation
“…Pison et al, 2013) or for a limited number of flux categories (e.g. Bergamaschi et al, 2013). Indeed, the assimilation of CH 4 observations alone, as reported in this synthesis, cannot fully separate individual sources, although sources with different locations or temporal variations could be resolved by the assimilated atmospheric observations.…”
Section: Definition Of Regions and Source Categoriesmentioning
confidence: 88%
“…Atmospheric inversions based on SCIAMACHY or GOSAT CH 4 retrievals have been carried out by different research groups (Monteil et al, 2013;Cressot et al, 2014;Alexe et al, 2015;Bergamaschi et al, 2013;Locatelli et al, 2015). For GOSAT, differences between the use of proxy and full-physics retrievals have been investigated.…”
Section: Satellite Data Of Column-averaged Chmentioning
confidence: 99%
“…At the same time, however, natural methane sources have the potential to significantly amplify human-induced climate change, for instance due to the strong dependence of methane wetland emissions on climate, release from permafrost soils and continental shelves, and potential destabilization of methane hydrates from the ocean floors [Kort et al, 2012;Walter-Anthony et al, 2012;Portnov et al, 2013]. While total global methane emissions from anthropogenic and natural processes at the Earth's surface are reasonably well determined [Bergamaschi et al, 2013], estimates of emissions by source sector vary by up to a factor of 2, and current ground-based observational networks fail to constrain methane emissions at regional scales [Dlugokencky et al, 2011]. with a Fourier transform interferometer like the Greenhouse Gases Observing Satellite.…”
Section: Introductionmentioning
confidence: 99%
“…The MERLIN data will primarily be supplied to inverse numerical models [Basu et al, 2013;Bergamaschi et al, 2013] that use the globally observed concentration gradients to infer methane surface fluxes with a foreseen grid resolution of 1000 km and a temporal resolution of 1 month, which represents a considerable improvement from the current state of the art. The MERLIN scientific advisory group set up a list of user requirements the mission has to fulfill to meet its goal.…”
Section: Introductionmentioning
confidence: 99%
“…The 4D-Var method is a popular inversion method and has been widely used in inversion studies for atmospheric carbon dioxide (CO 2 ) (e.g., Chevallier et al, 2005;Rödenbeck, 2005;Baker et al, 2006a), methane (CH 4 ) (e.g., Bergamaschi et al, 2013) and carbon monoxide (CO) (e.g., Kopacz et al, 2010;Hooghiemstra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%